2003
DOI: 10.1094/phyto.2003.93.10.1301
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobacteria-Mediated Growth Promotion of Tomato Leads to Protection AgainstCucumber mosaic virus

Abstract: We evaluated combinations of two strains of plant growth-promoting rhizobacteria (PGPR) formulated with the carrier chitosan for the ability to induce growth promotion of tomato plants and resistance to infection by Cucumber mosaic virus (CMV). Each PGPR combination included GB03 (Bacillus subtilis) and one of the following PGPR strains: SE34 (B. pumilus), IN937a (B. amyloliquefaciens), IN937b (B. subtilis), INR7 (B. pumilus), or T4 (B. pumilus). The PGPR combinations formulated with chitosan are referred to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 31 publications
4
77
0
Order By: Relevance
“…Several PGPB were formulated using chitosan as a carrier mixed with soilless growth medium for successful biological control against cucumber mosaic virus in tomato (Murphy et al 2003). Five PGPB were prepared into several formulations of polymers composed of carboxymethylcellulose starch.…”
Section: Polymeric Inoculants With Other Materialsmentioning
confidence: 99%
“…Several PGPB were formulated using chitosan as a carrier mixed with soilless growth medium for successful biological control against cucumber mosaic virus in tomato (Murphy et al 2003). Five PGPB were prepared into several formulations of polymers composed of carboxymethylcellulose starch.…”
Section: Polymeric Inoculants With Other Materialsmentioning
confidence: 99%
“…Both of these defense mechanisms are associated with disease resistance. ISR elicited by PGPR has shown promise in managing a wide spectrum of plant pathogens in several plant species under greenhouse and field environments (Radjacommare et al, 2004;Thangavelu et al 2004;Murphy et al, 2003). Fishal et al (2010) observed increased accumulation of resistance-related enzymes such as peroxidase (PO), phenylalanine ammonia lyase (PAL), lignithioglycolic acid (LTGA), and pathogenesis-related (PR) proteins (chitinase and -1, 3-glucanase) in banana plantlets treated with endophytic bacteria UPMP3 and UPMB3 singly or as mixture under glasshouse conditions.…”
Section: General Mode Of Action Of Antagonistic Bacteriamentioning
confidence: 99%
“…CMV strain Fny was provided by Peter Palukaitis (Scottish Crop Research Institute, Invergowrie, Scotland) and was used for all virus-based experiments in the current study. Leaf inoculation with CMV was performed as described previously by Ryu et al (2004b) and Murphy et al (2003). Briefly, CMV was maintained in N. tabacum cultivar Kentucky 14 by mechanical passage in a temperature-controlled greenhouse.…”
Section: −10mentioning
confidence: 99%